2019
DOI: 10.1186/s13287-019-1484-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteins of mesenchymal stem cell-derived extracellular vesicles

Abstract: Extracellular vesicles (EVs) contain proteins, microRNAs, mRNAs, long non-coding RNAs, and phospholipids, and are a novel mechanism of intercellular communication. It has been proposed that the immunomodulatory and regenerative effects of mesenchymal stem/stromal cells (MSCs) are mainly mediated by soluble paracrine factors and MSC-derived EVs (MSC-EVs). Recent studies suggest that MSC-EVs may serve as a novel and cell-free alternative to whole-cell therapies. The focus of this review is to discuss the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 80 publications
1
109
0
1
Order By: Relevance
“…The effects of MSC-derived exosomes have been primarily attributed to their cargo molecules, such as proteins, lipids, DNA and multiple RNA species [22][23][24][25]. In the present study, we demonstrated that labeled exosomes could cross the blood brain barrier (BBB) in the spine and migrate to the injured area.…”
Section: Discussionmentioning
confidence: 51%
“…The effects of MSC-derived exosomes have been primarily attributed to their cargo molecules, such as proteins, lipids, DNA and multiple RNA species [22][23][24][25]. In the present study, we demonstrated that labeled exosomes could cross the blood brain barrier (BBB) in the spine and migrate to the injured area.…”
Section: Discussionmentioning
confidence: 51%
“…MSC derived exosome exert their function have been mainly attributed to their cargo molecules such as proteins, lipids, DNAand multiple RNA species [22][23][24][25]. In the current study, we demonstrated that the label exosome could cross the blood brain barrier (BBB) in spinal and migrate to the injured area, as well as the transfer of their speci c cargo, the speci c presence of pro-angiogenic molecules, ANGPTL3 within exosome to damaged tissue.…”
Section: Discussionmentioning
confidence: 60%
“…Accumulating evidence has demonstrated that MSC-EVs modulate immune response by producing cytokines, growth factors, and tolerogenic molecules, such as IL-10, IL-6, IL-37, and lipocalin-2 and transforming growth factor (TGF)-β, programmed death ligand-1(PD-L1), galectin-1, etc. (20,23,24). Other than proteins, MSC-EVs are enriched with nucleic acids, including mRNA, microRNA (miRNA), and DNA (25).…”
Section: Characterization Of Msc-evs (Figure 1)mentioning
confidence: 99%